(untitled) (Ozone Therapy Global Journal, 2017)
Cutaneous ulcerations are a common clinical problem that appears with the increase in the average age of the population. The problems of scarring are not uncommon when there are predisposing factors such as arthritis Rheumatoid, diabetes, peripheral circulatory disorders, obesity, or previous scars. Some conditions of morbidity may be related to a deficiency of growth factors in the ulcerated site, such as the derived growth factor, platelet factor of epithelial growth factor vascular endothelial growth, resulting in a deficiency of the healing process. The key role of the growth factors in wound healing has stimulated significant research efforts aiming to test various products derived from platelets as treatments to improve the healing of chronic wounds. The rich fibrin platelet containing leukocytes (L-PRF) is a matrix 100% autologous derived from the blood of the patient and it contains no additives. The process of obtaining L-PRF concentrated platelets of 3 to 5 times the amount found in whole blood. Once platelets are activated by Thrombin autologous, begins the clotting cascade. The α granules in the platelets then release vital growth factors1. The combined use of this new biological material with ozone therapy in the treatment of skin ulcers represents a new synergy in the clinical experience designed to improve clinical outcomes. Explore this and other ideas designed to promote physiological harmony across the spectrum of the cure, it will be in benefit of our patients. .